Association of Xanthelasma palpebrarum (XP) with cardiovascular disease (CVD) risk factors - Suman, AHM Khairul Imam; Begum, Khadija; Rahman, Kaniz; Talukder, Abu Mohammed; Rahman, SM Matiur; Ali, Md Akmat; Hoque, Nusrath Jahan; Alam, Mohammad Morshad (Asian Journal of Medical and Biological Research, 2020)
Xanthelasma palpebrarum (XP) is the most common cutaneous xanthoma occurs over or surrounding the eyelids in yellowish color and various shapes. The objective of this study was to describe the status of cardiovascular disease risk factors in XP patients and determine their association with XP. A case-control study was conducted among 81 cases (have XP) and 81 controls (no XP) among patients attended for cardiac check-up between January 2019 to July 2019 at Ad-Din Women's Medical College Hospital, Dhaka, Bangladesh. Among 162 subjects were interviewed in our study, majority were female (62.3%). XP were found more prevalent among female and several cardiac risk factors were significantly associated with XP. The chi-square analysis indicates gender (p=0.035), BMI (p=0.01), Angina history (p=0.008), and serum LDL (p=0.024) were significantly associated with presence of XP. A higher percentage of patients with high total serum cholesterol, TG levels, and LDL was observed in patients with XP in compared to control group. Our study reveals an increased presence of cardiovascular disease risk factors among patients with xanthelasma. Moreover, a statistically significant association of gender, BMI, angina history, and serum LDL with XP were observed. Asian J. Med. Biol. Res. June 2019, 5(4): 324-329